SUSCEPTIBILITY PATTERNS OF COAGULASE-NEGATIVE STAPHYLOCOCCUS TO VARIOUS ANTIBIOTICS AT PAKISTAN INSTITUTE OF MEDICAL SCIENCE (The Research of Medical Science Review, 2025)
The rising prevalence of antibiotic resistance among bacterial pathogens in clinical settings is a critical global health concern. Coagulase-negative Staphylococcus spp. have emerged as significant nosocomial pathogens with a marked ability to resist multiple antimicrobial agents. This study investigates the antibiotic susceptibility patterns of 100 isolates of CoNS collected from clinical specimens at the Pakistan Institute of Medical Sciences. Through a cross-sectional analysis utilizing Kirby-Bauer disk diffusion methods, the sensitivity of isolates towards 12 different antibiotics was assessed. The results indicated a high sensitivity to vancomycin (97%) among CoNS isolates, while resistance was most common against penicillin-G, with 95% of isolates demonstrating resistance. The data underscore the necessity for vigilant antibiotic stewardship and highlight the utility of vancomycin as the first-line treatment for CoNS infections amidst the concerning backdrop of increasing antibiotic resistance. Consequently, this study serves to inform clinical practices and antibiotic policy-making, underscoring the urgency for ongoing surveillance and precise identification of resistance patterns to ensure effective pharmaceutical interventions.